2013
DOI: 10.4103/0019-5413.114939
|View full text |Cite
|
Sign up to set email alerts
|

Replantation of a circumferentially degloved ring finger by venous arterializations

Abstract: Treatment of ring degloving injuries of the finger is one of the most demanding problems in hand surgery. Replantation has been advocated as the best solution if the vessels belonging to the degloved skin are not irreversibly destroyed. We present a case involving a ring finger with circumferentially avulsed skin. Debridement under microscopy showed that the peeled skin did not retain any arteries, but did have various superficial veins of good caliber. The neurovascular bundles of the finger remained in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Others have suggested vein arterialization as a valid approach to re-establish the blood supply of a degloved finger — as long as physiologic circulation restoration is not possible and veins in the degloved tissue are not damaged. [ 33 34 ]…”
Section: Introductionmentioning
confidence: 99%
“…Others have suggested vein arterialization as a valid approach to re-establish the blood supply of a degloved finger — as long as physiologic circulation restoration is not possible and veins in the degloved tissue are not damaged. [ 33 34 ]…”
Section: Introductionmentioning
confidence: 99%
“…Our past clinical experience in vein arterialization had revealed that process of revascularization can be lagging. 3 4 Based on this, we decided not to give up the replanted finger at the request of the patient. The finger did not become dark red until 9 h after the replantation.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, as a remedial measure and an alternative to conventional replantation, vein arterialization has raised widespread interest in this area of the replantation surgery. 3 4 5 The unique characteristic of its nonphysiological blood supply requires special implementations through intraoperative vascular monitoring. Comprehending phenomenon will improve the success rate of this unusual replantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes it is impossible to perform an arterial anastomosis even with the interposition of a long venous graft [ 1 ]. Although the absence of anastomosed vessels constitutes a contraindication in replantation, the need for arterial vessels in good condition has recently been questioned in recent literature, where some authors have proposed the arterialization of veins with promising results [ 2 3 ]. However, this method of rescuing the amputated segments is not routine, and it is not clear what conditions can establish venous congestion [ 3 ].…”
Section: Introductionmentioning
confidence: 99%